2003
DOI: 10.1046/j.1365-2265.2003.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating pattern and the effect of oral glucose on ghrelin and insulin secretion in patients with anorexia nervosa

Abstract: These findings suggest that differences in eating behaviour in AN may induce alterations in both ghrelin and insulin metabolism in the acute feeding state. Furthermore, metabolic changes in the restrictive eating pattern may be related to the pathophysiology of small quantitative meal intake in AN-R patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Although differences in the speed of meal consumption across groups likely affected our data, the fact that the AUC analysis also yielded significant group differences argues that these differences cannot be attributed solely to differential rates of food consumption between groups. Interestingly, studies using an OGTT have also found a delay in the insulin response curve in both ill (39) and weight-restored AN subjects (10). Gastric and gut dysmotility associated with AN (26,34) may be an additional factor contributing to the right shift in glucose and insulin response curves observed in AN compared with control subjects, and the lower AUC for glucose and insulin in starved AN may reflect malabsorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although differences in the speed of meal consumption across groups likely affected our data, the fact that the AUC analysis also yielded significant group differences argues that these differences cannot be attributed solely to differential rates of food consumption between groups. Interestingly, studies using an OGTT have also found a delay in the insulin response curve in both ill (39) and weight-restored AN subjects (10). Gastric and gut dysmotility associated with AN (26,34) may be an additional factor contributing to the right shift in glucose and insulin response curves observed in AN compared with control subjects, and the lower AUC for glucose and insulin in starved AN may reflect malabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of glucose levels and insulin secretion in AN, for example, mixed results may be attributed to the use of oral glucose tolerance tests (OGTT) or liquid meals (10,39,47) rather than a mixed macronutrient solid meal representative of what patients are fed in a standard behavioral treatment program for AN. Furthermore, most studies have administered a test meal or OGTT only at the start of treatment in the starved state (39,47) or have failed to specify at what point in refeeding subjects were tested (42). When studies have examined responses to a solid meal they have often been limited to sample sizes of less than 10 subjects per group (see Ref.…”
mentioning
confidence: 99%
“…It remains to be clarified whether salivary ghrelin might be a useful tool in clinical chemistry for diagnosis of metabolic or gastrointestinal disorders as has been postulated for serum ghrelin (49,50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al in 2003 found higher plasma levels of ghrelin in patients with AN Purging (AN-P) than in AN-R [59][60][61] . In 2004, the group of Tanaka replicated their findings in a later study which included a third subgroup of AN, a subgroup that required emergency hospitalization; in this group the patients were unable to eat and had an extreme loss of weight.…”
Section: Ghrelin and The Regulation Of Appetitementioning
confidence: 99%
“…However, the Troisi group compared data between patients with AN-P and BN, which probably had a higher BMI, which may explain the difference between the results of the two studies. There seems to be a relationship between ghrelin concentrations and patients with the compulsive/purging subtype for both AN (AN-P) and for BN [59][60][61] . However, this finding has still not reached a consensus, Monteleone et al 2008 47 found no significant difference in the concentration of plasma ghrelin when fasting in groups with AN-R and AN-P. One explanation for these conflicting results is the method used to measure ghrelin and how it was performed, the preference for using plasma or serum can affect the levels obtained in different studies.…”
Section: Ghrelin and The Regulation Of Appetitementioning
confidence: 99%